Lightweight cement-based composite material for spraying engineering as well as preparation method and application of lightweight cement-based composite material
By optimizing the ratio and process of lightweight jet engineering cement-based composite materials, the problems of poor adhesion, high rebound rate and limited jet thickness of traditional jet ECC materials are solved, and the lightweight and performance improvement of the material is achieved. In engineering applications.
Patent Information
- Application Number
- CN202411354131.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Traditional jet ECC materials have problems such as poor adhesion, high rebound rate and limited jet thickness, which limit their application in engineering.
Use lightweight jet engineering cement-based composite materials composed of cement, fly ash, silicon fume, hollow fly ash microbeads, organic fibers, water reducers and thickeners to improve the material by adjusting the ratio and process flow. Adhesion and mechanical properties reduce rebound rate and achieve a larger jet thickness.
It significantly improves the adhesion and mechanical properties of the material, reduces the rebound rate and density, makes it comply with the lightweight concrete standards, is suitable for engineering applications, and improves the construction efficiency and the practical application value of the material.
Smart Images

Figure CN119241164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering materials, and in particular relates to a lightweight spraying engineering cement-based composite material and a preparation method and application thereof. Background Art
[0002] Engineered cementitious composite (ECC) is a cement-based composite material with ultra-high ductility. Its ultimate tensile strain under uniaxial load can reach more than 3%, and it has good strain hardening performance. However, the traditional casting process has shortcomings such as long construction period and the need for formwork, which limits its wide application in engineering. Sprayed ECC technology can not only overcome the shortcomings of traditional cast ECC but also improve construction efficiency by applying ECC materials to the substrate surface in the form of a spray. However, traditional sprayed ECC has problems such as poor adhesion, high rebound rate and limited spraying thickness. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a lightweight spraying engineering cement-based composite material and a preparation method and application thereof, wherein the material has excellent adhesion and mechanical properties, and exhibits low rebound rate and large spraying thickness during the spraying process.
[0004] In order to achieve the above object, the present invention provides the following technical solutions:
[0005] The present invention provides a lightweight spraying engineering cement-based composite material, which comprises the following components in parts by mass:
[0006] 210-600 parts of cement, 100-700 parts of fly ash, 70-100 parts of silica fume, 110-385 parts of hollow fly ash microspheres, 255-316 parts of water, 15-20 parts of organic fiber, 3.5-6 parts of water reducer and 0.3-0.4 parts of thickener.
[0007] Preferably, the cement is OPC type 525 ordinary Portland cement.
[0008] Preferably, the fly ash is primary fly ash.
[0009] Preferably, the particle size of the hollow fly ash microbeads is 1 to 300 μm.
[0010] Preferably, the organic fibers include polyethylene fibers; and the lengths of the organic fibers include 6 mm and 12 mm.
[0011] Preferably, the water reducer is a polycarboxylate high-efficiency water reducer.
[0012] Preferably, the thickener comprises hydroxypropyl methylcellulose.
[0013] The present invention also provides a method for preparing the lightweight sprayed engineering cement-based composite material described in the above technical solution, comprising the following steps:
[0014] Firstly mixing cement, fly ash, silica fume and hollow fly ash microbeads to obtain a dry powder mixture;
[0015] The dry powder mixture, part of water and part of water reducing agent are mixed for a second time, and then the remaining water, remaining water reducing agent and thickener are added for a third time, and finally organic fiber is added for dispersion to obtain the lightweight spraying engineering cement-based composite material.
[0016] The present invention also provides the use of the lightweight sprayed engineering cement-based composite material described in the above technical solution or the lightweight sprayed engineering cement-based composite material prepared by the preparation method described in the above technical solution in building construction.
[0017] Preferably, the application method includes:
[0018] After spraying the lightweight sprayed engineering cement-based composite material onto the surface of the substrate, curing is performed;
[0019] The diameter of the nozzle used for the spraying is 6-10 mm; the air flow pressure of the spraying is 0.6-1 MPa; the spraying thickness of the spraying is ≤25 mm; and the spraying is layered spraying.
[0020] The present invention provides a lightweight spraying engineering cement-based composite material, which comprises the following components in parts by mass:
[0021] 210-600 parts of cement, 100-700 parts of fly ash, 70-100 parts of silica fume, 110-385 parts of hollow fly ash microspheres, 255-316 parts of water, 15-20 parts of organic fiber, 3.5-6 parts of water reducer and 0.3-0.4 parts of thickener.
[0022] The present invention not only significantly reduces the density of the sprayed ECC by adding hollow fly ash microspheres (FAC) to make it meet the standard of "Technical Specification for Lightweight Aggregate Concrete" JGJ-51-2002, which is lower than 1950kg / m 3 In order to meet the requirements of lightweight concrete, the lightweight of the material is achieved, and the fluidity, adhesion and mechanical properties (tensile strength) of the material are greatly improved. The problems of poor adhesion, high rebound rate and limited spraying thickness of traditional sprayed ECC are solved. During the spraying process, it shows a lower rebound rate and a larger spraying thickness, providing a lightweight sprayed engineering cement-based composite material with excellent performance for engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the spraying principle of lightweight spraying engineering cement-based composite materials;
[0024] Figure 2 This is a diagram of the density test method;
[0025] Figure 3 This is the cube compression test diagram;
[0026] Figure 4 This is a diagram of the tensile test device;
[0027] Figure 5 This is the test diagram of the four-point bending test;
[0028] Figure 6 The spraying morphology and spraying thickness diagram of the lightweight spraying engineering cement-based composite material prepared in Examples 1 to 3;
[0029] Figure 7 The spraying morphology and spraying thickness diagram of the lightweight spraying engineering cement-based composite material prepared in Examples 4 to 6;
[0030] Figure 8 This is a floatability test diagram of the lightweight sprayed engineering cement-based composite material prepared in Example 6. DETAILED DESCRIPTION
[0031] The present invention provides a lightweight spraying engineering cement-based composite material, which comprises the following components in parts by mass:
[0032] 210-600 parts of cement, 100-700 parts of fly ash, 70-100 parts of silica fume, 110-385 parts of hollow fly ash microspheres, 255-316 parts of water, 15-20 parts of organic fiber, 3.5-6 parts of water reducer and 0.3-0.4 parts of thickener.
[0033] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0034] The lightweight spraying engineering cement-based composite material provided by the present invention comprises 210 to 600 parts by mass of cement, preferably 300 to 600 parts by mass. In the present invention, the cement is preferably OPC type 525 ordinary Portland cement.
[0035] The lightweight sprayed engineering cement-based composite material provided by the present invention comprises 100 to 700 parts by mass of fly ash, preferably 200 to 420 parts by mass, based on 1 part by mass of cement. In the present invention, the fly ash is preferably first-grade fly ash; the particle size of the fly ash is preferably 1 to 100 μm, more preferably 10 to 50 μm; the specific surface area of the fly ash is preferably 200 to 500 cm 2 / g, more preferably 300 to 400 cm 2 / g, and the density is preferably 2.1 to 2.6 g / cm3 .
[0036] The density of fly ash is usually low (2.1-2.6 g / cm 3 ), compared with ordinary Portland cement (3.1~3.2g / cm 3 ) is much lighter. Therefore, the use of fly ash can reduce the overall density of the material, thereby achieving a lightweight effect. The fine and spherical particles of fly ash can act as a lubricant, reduce the viscosity of the mixture, and significantly improve the fluidity of the mixture. This helps to make it easier to pump and pour during construction, reducing the difficulty and time of construction. Fly ash can improve the adhesion of the material because its fine particles can fill the pores in the cement matrix and increase the density and adhesion of the material. For shotcrete, good adhesion can ensure that the material adheres better to the substrate and reduce the possibility of falling off and cracking. The active ingredients of fly ash (such as silicates and aluminates) can generate secondary hydration products (such as CSH gel) with calcium hydroxide in cement during the hydration reaction, enhancing the strength and durability of concrete. Rebound performance: The fine particles and good lubricity of fly ash can reduce the amount of rebound of the material during the spraying process, reduce material waste, and improve construction efficiency. The improvement of the fluidity and adhesion of fly ash helps to control the thickness of the spraying layer. Better fluidity allows the shotcrete to be distributed more evenly, while better adhesion ensures that the material does not fall off easily when the required thickness is reached.
[0037] The lightweight spraying engineering cement-based composite material provided by the present invention comprises 70 to 100 parts by mass of silica fume, preferably 80 to 100 parts by mass, based on 1 part by mass of cement. In the present invention, the particle size of the silica fume is preferably 0.01 to 1.0 μm, more preferably 0.1 to 1.0 μm; the specific surface area of the silica fume is preferably 15000 to 30000 m 2 / kg, more preferably 20000 to 25000m 2 / kg; the mass percentage of SiO2 in the silica ash is preferably 90-95%, more preferably 91-92.26%.
[0038] The ultrafine particles of silica fume can increase the viscosity of the slurry, reduce segregation and bleeding, and thus significantly improve the fluidity of the mixture with the appropriate water reducer. This helps to make pumping and pouring easier during construction, reducing the difficulty and time of construction. Silica fume can significantly improve the adhesion of materials because its ultrafine particles can fill the tiny pores in the cement matrix, increasing the density and bonding of the material. For shotcrete, good adhesion can ensure that the material adheres better to the substrate and reduce the possibility of falling off and cracking. The highly active components of silica fume can react secondary with calcium hydroxide generated by cement hydration to generate more CSH gel, thereby significantly improving the compressive strength, flexural strength and durability of concrete. Silica fume can also improve the crack resistance and impermeability of the material and improve the overall mechanical properties of the material. In shotcrete, rebound rate is an important performance indicator. The fine particles and high viscosity of silica fume can reduce the amount of rebound of the material during the spraying process, reduce material waste and improve construction efficiency. The improvement of the fluidity and adhesion of silica fume helps to control the thickness of the spraying layer. Better fluidity allows the shotcrete to be distributed more evenly, while better adhesion ensures that the material does not fall off easily when the required thickness is reached.
[0039] The lightweight spraying engineering cement-based composite material provided by the present invention comprises 110 to 385 parts by mass of hollow fly ash microspheres, preferably 165 to 300 parts by mass, based on 1 part by mass of cement. In the present invention, the particle size of the hollow fly ash microspheres is preferably 1 to 300 μm, more preferably 100 to 200 μm; the wall thickness of the hollow fly ash microspheres is preferably 2 to 5 μm, more preferably 3 to 4 μm; the specific surface area of the hollow fly ash microspheres is preferably 350 to 500 m 2 / kg, more preferably 400 to 450 m 2 / kg, the density is preferably 0.6-0.8g / cm 3 , more preferably 0.65 to 0.75 g / cm 3 The bulk density of the hollow fly ash microspheres is preferably 500-600 kg / m 3 , more preferably 520-550 kg / m 3 The apparent specific gravity of the hollow fly ash microspheres is preferably 1100-1300 kg / m 3 , more preferably 1150 to 1200 kg / m 3 .
[0040] The density of hollow fly ash microspheres is extremely low (usually 0.6-0.8 g / cm 3 ), which is much lower than ordinary cement (about 3.1-3.2 g / cm 3) and other conventional aggregates. The addition of hollow fly ash microspheres can significantly reduce the overall density of the material, thereby achieving a lightweight effect. This is particularly important for reducing the deadweight of the structure and improving the seismic performance of the building. Fluidity: The spherical particle structure of the hollow fly ash microspheres helps to improve the fluidity of the mixture. Its smooth surface and spherical structure can reduce the internal friction of the mixture, making the slurry easier to flow during mixing and pumping, and improving the convenience and efficiency of construction. Adhesion performance: The hollow fly ash microspheres can fill the pores in the cement matrix, improve the density and adhesion of the material, and its spherical structure can also increase the lubricity of the slurry and improve the adhesion between the material and the substrate, which is particularly important for shotcrete, and can reduce the shedding and waste of materials during construction. Mechanical properties: Although hollow fly ash microspheres are mainly used to reduce the density of materials, their high-strength shell structure can also improve the compressive strength and crack resistance of the material to a certain extent. In addition, hollow fly ash microspheres can optimize the particle grading of the material and improve the overall mechanical properties of the material. Resilience: In shotcrete construction, the rebound rate is a key performance indicator. The addition of hollow fly ash microspheres can significantly reduce the amount of rebound during the spraying process, because its spherical particles can better embed into the surface of the substrate, improve the adhesion of the material, thereby reducing material waste and improving construction efficiency. Thickness control: The improvement in the fluidity and adhesion of hollow fly ash microspheres helps to better control the thickness of the sprayed layer. Its good fluidity allows the sprayed concrete to be more evenly distributed, while its excellent adhesion ensures that the material is not easy to fall off when the required thickness is reached.
[0041] Based on 1 mass part of cement, the lightweight sprayed engineering cement-based composite material provided by the present invention comprises 255 to 316 mass parts of water, preferably 260 to 316 mass parts.
[0042] The lightweight spraying engineering cement-based composite material provided by the present invention comprises 15 to 20 parts by mass of organic fibers, preferably 17 to 20 parts by mass, based on 1 part by mass of cement. In the present invention, the organic fibers comprise polyethylene fibers; the lengths of the organic fibers include 6 mm and 12 mm; the mass ratio of the organic fibers with a length of 6 mm to the organic fibers with a length of 12 mm is preferably 0.8 to 1:1, more preferably 1:1; the diameter of the organic fibers is preferably 20 to 25 μm, more preferably 24 μm.
[0043] Fluidity: Organic fibers have a dual effect on the fluidity of the material. Although the addition of fibers will increase the viscosity of the slurry and slightly reduce the fluidity, good fluidity can still be maintained by reasonably controlling the fiber content and using appropriate water reducers. At the same time, the presence of fibers can prevent the material from segregating or bleeding during pumping and construction, thereby improving "workability". "Workability" refers to the ease of operation and processability of the material during the construction process, specifically including the following aspects: Fluidity: whether the material is easy to flow, fill molds or structural gaps, and whether it is easy to construct and pump; Cohesion: whether the material remains uniform during the flow process to prevent segregation or bleeding; Plasticity: the operability of the material during the molding process, such as whether it is easy to smooth and compact; Water retention: whether the material can maintain appropriate moisture during the construction process to avoid construction difficulties or quality problems caused by excessive water loss.
[0044] Adhesion properties: Organic fibers can enhance the adhesion between the material and the substrate. The fibers are dispersed inside the material to form a three-dimensional network structure, which helps to improve the overall adhesion of the material. This enhancement effect is particularly evident in shotcrete, which can ensure that the material adheres better to the substrate and reduce the shedding of the material during construction. Mechanical properties: Organic fibers significantly improve the crack resistance and toughness of the material. The fibers play a bridging role in the material, which can prevent the formation and expansion of cracks, thereby improving the tensile strength and fracture toughness of the material. This is very beneficial for shotcrete in terms of early strength development and long-term durability. Resilience: In shotcrete construction, organic fibers can reduce the rebound rate of the material. The presence of fibers increases the internal friction of the material, making it easier for the shotcrete to adhere to the surface of the substrate, reducing the amount of rebound during the shotcrete process, thereby improving the utilization rate of the material and reducing waste. Thickness control: The reinforcement effect of organic fibers helps to better control the spraying thickness of the material during shotcrete construction. Fiber-reinforced materials show good adhesion and stability when sprayed in layers, which can ensure good bonding between the layers and avoid cracking or peeling between the layers, thereby ensuring the uniformity and required thickness of the sprayed layer.
[0045] The lightweight spraying engineering cement-based composite material provided by the present invention comprises 3.5 to 6 parts by mass of a water reducer, preferably 3.5 to 5 parts by mass, based on 1 part by mass of cement. In the present invention, the water reducer is preferably a polycarboxylate high-efficiency water reducer; the water reduction rate of the water reducer is preferably 20 to 30%, more preferably 22 to 25%.
[0046] Based on 1 mass part of cement, the lightweight spraying engineering cement-based composite material provided by the present invention comprises 0.3 to 0.4 mass parts of thickener, preferably 0.3 mass parts. In the present invention, the thickener preferably comprises hydroxypropyl methylcellulose.
[0047] Fluidity: One of the main functions of thickeners is to adjust the fluidity of the slurry. Although thickeners increase the viscosity of the slurry and may slightly reduce its fluidity, the proper use of thickeners can prevent the material from segregating or bleeding during pumping or spraying, thereby maintaining good construction performance. In addition, thickeners can help maintain proper fluidity at low water-cement ratios and optimize the workability of the material. Adhesion Performance: Thickeners can significantly improve the adhesion performance of materials. By increasing the viscosity of the slurry, thickeners enhance the bond between the material and the substrate, ensuring that the material adheres better to the substrate surface when sprayed. This is critical to ensuring the stability of the shotcrete and reducing material shedding.
[0048] The lightweight sprayed engineering cement-based composite material provided by the present invention has excellent fluidity, good adhesion performance and remarkable mechanical properties. In particular, in the case of high-content hollow fly ash microspheres (FAC), it exhibits a floating characteristic and is suitable for engineering applications for reducing the deadweight of structures and improving construction efficiency, such as the reinforcement of components such as beams, columns, beam-column joints, walls and panels, and has good practical engineering application value.
[0049] The lightweight sprayed engineering cement-based composite material provided by the present invention is also suitable for the reinforcement of tunnels and underground structures. Tunnels and underground structures usually require materials with good fluidity and rapid solidification properties so that they can be effectively constructed in a small space. The material of the present invention can quickly fill and reinforce these structures, enhance their water resistance, impermeability and compression resistance, reduce maintenance costs and extend the life of the structure.
[0050] The present invention also provides a method for preparing the lightweight sprayed engineering cement-based composite material described in the above technical solution, comprising the following steps:
[0051] Firstly mixing cement, fly ash, silica fume and hollow fly ash microbeads to obtain a dry powder mixture;
[0052] The dry powder mixture, part of water and part of water reducing agent are mixed for a second time, and then the remaining water, remaining water reducing agent and thickener are added for a third time, and finally organic fiber is added for dispersion to obtain the lightweight spraying engineering cement-based composite material.
[0053] In the present invention, the first mixing is preferably carried out at a low speed; the low speed is preferably 140 r / min of rotation and 62 r / min of revolution; the time of the first mixing is preferably 2 min.
[0054] In the present invention, the second mixing is preferably carried out at a high speed; the high speed is preferably 285 r / min of rotation and 125 r / min of revolution; the time of the second mixing is preferably 3 min.
[0055] In the present invention, the third mixing is preferably stirred at a high speed gear; the high speed gear is preferably a rotation of 285r / min and a revolution of 125r / min; the time of the third mixing is preferably 3min; the mass ratio of the partial water to the remaining water is preferably 0.8 to 1:1, more preferably 1:1; the mass ratio of the partial water reducer to the remaining water reducer is preferably 0.8 to 1:1, more preferably 1:1.
[0056] In the present invention, the dispersion is preferably stirred at a low speed; the low speed is preferably 140 r / min of rotation and 62 r / min of revolution; the dispersion time is preferably 120 s.
[0057] The present invention also provides the use of the lightweight sprayed engineering cement-based composite material described in the above technical solution or the lightweight sprayed engineering cement-based composite material prepared by the preparation method described in the above technical solution in building construction.
[0058] In the present invention, the application method preferably includes: spraying the lightweight sprayed engineering cement-based composite material onto the surface of the substrate and then curing it. In the present invention, the equipment used for the spraying is preferably a spray gun, more preferably a 9511 type handheld mortar spray gun; the diameter of the nozzle used for the spraying is preferably 6-10 mm, more preferably 8 mm; the distance between the nozzle used for the spraying and the surface of the substrate is preferably 20-40 cm, more preferably 30 cm; the air flow pressure of the spraying is preferably 0.6-1 MPa, more preferably 0.8 MPa; the spraying thickness of the spraying is preferably ≤25 mm, more preferably 20 mm; the spraying is preferably layered spraying; the thickness of each layer of spraying is preferably 10-15 mm, more preferably 12-14 mm; the curing is preferably carried out in a curing room; the curing temperature is preferably 20-25 ° C, more preferably 23 ° C; the relative humidity of the curing is preferably 90-95%, more preferably 95%; the curing time is preferably 14-28 d, more preferably 28 d.
[0059] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0060] Examples 1 to 6
[0061] The component proportions of the lightweight sprayed engineering cement-based composite materials in Examples 1 to 6 are shown in Table 1.
[0062] Table 1 Component ratio of lightweight spraying engineering cement-based composite materials in Examples 1 to 6 (kg / m 3 )
[0063]
[0064] The characteristics of the raw materials used are as follows:
[0065] The cement is OPC type 525 ordinary Portland cement, which comes from Zhucheng Yangchun Shanshui Co., Ltd.;
[0066] The fly ash is first-grade fly ash with a particle size of 1 to 100 μm and a specific surface area of 200 to 500 cm 2 / g, density is 2.1~2.6g / cm 3 , from Gongyi Borun Refractory Materials Co., Ltd.;
[0067] The particle size of silica fume is 0.01-1.0 μm, and the specific surface area is 15000-30000 m 2 / kg, the mass percentage of SiO2 in silica ash is 92.26%, which comes from Henan Borun New Materials Co., Ltd.;
[0068] The particle size of hollow fly ash microspheres is 1-300 μm, the wall thickness is 2-5 μm, and the specific surface area is 400 m 2 / kg, the density is preferably 0.6g / cm 3 , bulk density is 550kg / m 3 , apparent density is 1200kg / m 3 , from Gongyi Borun Refractory Materials Co., Ltd.;
[0069] The length of polyethylene fiber includes 6mm and 12mm, the diameter is 24μm, and it comes from a domestic fiber material supplier;
[0070] Polycarboxylate high-efficiency water-reducing agent, with a water-reducing rate of 30%, is sourced from Sika (Jiangsu) Building Materials Co., Ltd.;
[0071] The type of thickener is hydroxypropyl methylcellulose (CMC), which comes from Jinzhou Baoyi Building Materials Technology Co., Ltd.;
[0072] The method for preparing the lightweight sprayed engineering cement-based composite material comprises the following steps:
[0073] Cement, fly ash, silica fume and hollow fly ash microbeads are added into a stirring pot, stirred at a low speed (rotation 140 r / min, revolution 62 r / min) for 2 min to fully mix all the dry powders to obtain a dry powder mixture; half of the required amount of water and water reducer is weighed and added into the stirring pot, stirred at a high speed (rotation 285 r / min, revolution 125 r / min) for 3 min, then the remaining water, remaining water reducer and thickener are added, and stirred at a high speed for 3 min, polyethylene fibers are manually dispersed, and polyethylene fibers are slowly added at a low speed and stirred for 120 s to check whether there is fiber agglomeration to obtain the lightweight injection engineering cement-based composite material.
[0074] Comparative Example 1
[0075] 1) Raw material ratio: the raw materials are shown in Table 2.
[0076] Table 2 Raw material formula in comparative example 1
[0077] Material Name <![CDATA[Usage / (kg / m 3 )]]> Quality Ratio cement 489 1.00 fine aggregate / sand 852 1.74 Coarse aggregate / stone 670 1.37 Mixing water 215 0.44 Admixture / Polycarboxylate Water Reducer 24.45 0.050 PVA fiber 1.2 0.0024
[0078] 2) Mixing: gravel + sand + cement + fiber (mix and stir for 30-60 seconds) + a mixture of water and polycarboxylate water-reducing agent (stir until complete); you can also add the fiber to the mixture of water and polycarboxylate water-reducing agent and stir and disperse it, then add it to the mixer and mix with other materials;
[0079] 3) After mixing is completed, random sampling is performed. If the fibers have been evenly dispersed into single filaments, the concrete can be put into use; if there are still bundled fibers, the mixing time should be extended by 30 to 60 seconds.
[0080] Comparative Example 2
[0081] The difference from Example 5 is that no hollow fly ash microbeads are added.
[0082] Comparative Example 3
[0083] The difference from Example 5 is that no silica fume is added.
[0084] Application Example 1
[0085] The lightweight sprayed engineering cement-based composite material prepared in Example 1 was poured into a spray gun (9511 type handheld mortar spray gun, nozzle diameter 8mm, airflow pressure 0.8MPa), ensuring that the spray gun was kept 30cm away from the substrate surface, and the spraying thickness was controlled within 25mm. Layered spraying was performed, and the spraying thickness of each layer was controlled within 10-15mm. During the spraying process, attention was paid to uniform spraying to avoid clogging of the spray gun. After the spraying was completed, the sprayed specimen was placed in a curing room (temperature 23°C, relative humidity 95%) and cured for 28d to ensure that the specimen reached the optimal strength under constant temperature and humidity conditions.
[0086] Application Example 2
[0087] The difference from Application Example 1 is that the lightweight sprayed engineering cement-based composite material prepared in Example 1 is replaced by the lightweight sprayed engineering cement-based composite material prepared in Example 2.
[0088] Application Example 3
[0089] The difference from Application Example 1 is that the lightweight sprayed engineering cement-based composite material prepared in Example 1 is replaced by the lightweight sprayed engineering cement-based composite material prepared in Example 3.
[0090] Application Example 4
[0091] The difference from Application Example 1 is that the lightweight sprayed engineering cement-based composite material prepared in Example 1 is replaced by the lightweight sprayed engineering cement-based composite material prepared in Example 4.
[0092] Application Example 5
[0093] The difference from Application Example 1 is that the lightweight sprayed engineering cement-based composite material prepared in Example 1 is replaced by the lightweight sprayed engineering cement-based composite material prepared in Example 5.
[0094] Comparative application example 1
[0095] The difference from Application Example 5 is that the lightweight spraying engineering cement-based composite material prepared in Example 1 is replaced by the cement-based composite material prepared in Comparative Example 1.
[0096] Comparative Application Example 2
[0097] The difference from Application Example 5 is that the lightweight spraying engineering cement-based composite material prepared in Example 1 is replaced by the cement-based composite material prepared in Comparative Example 2.
[0098] Comparative Application Example 3
[0099] The difference from Application Example 5 is that the lightweight spraying engineering cement-based composite material prepared in Example 1 is replaced by the cement-based composite material prepared in Comparative Example 3.
[0100] Performance Testing
[0101] The properties of the lightweight spraying engineering cement-based composite materials prepared in Examples 1 to 6 and the cement-based composite materials prepared in Comparative Examples 1 to 3 were tested. The results are shown in Table 3. The test method is as follows:
[0102] Fluidity test: GB / T2419-2005 "Method for determination of fluidity of cement mortar" was used. Equipment: NLD-3 cement mortar fluidity tester. Steps: According to GB / T2419-2005 standard, the newly mixed LSECC was loaded into the cone mold in two layers, and each layer was evenly compacted with a tamping rod. After the vibration was completed, the diameter after diffusion was measured with a ruler, and the average value was calculated as the fluidity.
[0103] Maximum spray thickness test: Equipment: gypsum board, steel ruler. Steps: Continuously spray LSECC onto the vertical gypsum board until a certain thickness is reached and the LSECC starts to slide off. Use a steel ruler to measure the maximum spray thickness.
[0104] Density test: Use the drainage method to measure, equipment: constant temperature drying oven, electronic scale, measuring cup. Steps: After drying the test block to constant weight, measure its mass and volume. Calculate the density based on mass and volume, as follows: Figure 2 shown.
[0105] Compressive strength test: Equipment: MTS200T pressure testing machine. Steps: Place the test block in the loading center of the testing machine, use force control, and the loading rate is 200N / S. Measure the ultimate compressive strength of the cubic test block, and calculate the compressive strength according to the formula σm=F / A, as follows Figure 3 shown.
[0106] Tensile strength test: Equipment: 300kN MTS microcomputer controlled electronic universal testing machine. Procedure: Perform uniaxial tensile test according to the recommendations of the Japan Society of Civil Engineers (JSCE). The dog bone specimen gauge length is 80mm and the loading rate is 1mm / min. Measure the tension and elongation, calculate the stress and strain, such as Figure 4 shown.
[0107] Four-point bending test: Equipment: 30t universal testing machine, VIC-3D system. Steps: ECC was sprayed onto the fine stone concrete layer prepared in the mold with a spraying thickness of 20mm. After curing for 28 days, a four-point bending test was carried out with a displacement control rate of 0.5mm / min. The VIC-3D system was used to conduct non-contact testing of strain and crack development, such as Figure 5 shown.
[0108] Table 3 Properties of lightweight sprayed engineering cement-based composite materials prepared in Examples 1 to 6
[0109]
[0110] As shown in Table 3, the fluidity of the lightweight sprayed engineering cement-based composite materials prepared in Examples 1 to 6 ranges from 135 to 190 mm, the maximum spray thickness ranges from 28 to 55 mm, and the density ranges from 960 to 1630 kg / m 3 The compressive strength ranges from 15.45 to 51.2 MPa, the tensile strength ranges from 2.4 to 5.6 MPa, and the ultimate tensile strain ranges from 4.4 to 6.6%.
[0111] Figure 6 The spraying morphology and spraying thickness diagram of the lightweight spraying engineering cement-based composite material prepared in Examples 1 to 3 are as follows: Figure 7 The spraying morphology and spraying thickness of the lightweight spraying engineering cement-based composite material prepared in Examples 4 to 6. Figures 6-7It can be seen that the maximum spraying thickness of the lightweight spraying engineering cement-based composite material prepared by the present invention can reach 25mm, and according to the principle of layered multiple spraying, a more considerable spraying thickness can be formed layer by layer. After the content of hollow fly ash microspheres reaches 50%, its single maximum spraying thickness is significantly improved, among which the maximum spraying thickness of the LSECC70 formula reaches 55mm. The lightweight spraying engineering cement-based composite material can adhere well to the substrate because the maximum adhesion it can provide can maintain its own weight. Therefore, after the content of hollow fly ash microspheres exceeds 50%, its density drops rapidly and its own gravity also decreases rapidly. Therefore, it can maintain a larger spraying thickness under the condition of equivalent adhesion.
[0112] Figure 8 This is a test diagram of the floatability of the lightweight sprayed engineering cement-based composite material prepared in Example 6. Figure 8 It can be seen that the density of the lightweight sprayed engineering cement-based composite material (LSECC70) prepared in Example 6 is 960 kg / m 3 , and has the property of floating.
[0113] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A lightweight spraying engineering cement-based composite material, characterized in that: In parts by mass, it includes the following components: 210-600 parts of cement, 100-700 parts of fly ash, 70-100 parts of silica fume, 110-385 parts of hollow fly ash microspheres, 255-316 parts of water, 15-20 parts of organic fiber, 3.5-6 parts of water reducer and 0.3-0.4 parts of thickener.
2. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The cement is OPC type 525 ordinary Portland cement.
3. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The fly ash is primary fly ash.
4. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The particle size of the hollow fly ash microbeads is 1 to 300 μm.
5. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The organic fibers include polyethylene fibers; and the lengths of the organic fibers include 6 mm and 12 mm.
6. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The water reducing agent is a polycarboxylate high efficiency water reducing agent.
7. The lightweight spraying engineering cement-based composite material according to claim 1, characterized in that: The thickening agent includes hydroxypropyl methylcellulose.
8. The method for preparing the lightweight spraying engineering cement-based composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Firstly mixing cement, fly ash, silica fume and hollow fly ash microbeads to obtain a dry powder mixture; The dry powder mixture, part of water and part of water reducing agent are mixed for a second time, and then the remaining water, remaining water reducing agent and thickener are added for a third time, and finally organic fiber is added for dispersion to obtain the lightweight spraying engineering cement-based composite material.
9. Use of the lightweight sprayed engineering cement-based composite material according to any one of claims 1 to 7 or the lightweight sprayed engineering cement-based composite material prepared by the preparation method according to claim 8 in building construction.
10. The use according to claim 9, characterized in that: The application methods include: After spraying the lightweight sprayed engineering cement-based composite material onto the surface of the substrate, curing is performed; The diameter of the nozzle used for the spraying is 6-10 mm; the air flow pressure of the spraying is 0.6-1 MPa; the spraying thickness of the spraying is ≤25 mm; and the spraying is layered spraying.
Citation Information
Patent Citations
Sprayable ultrahigh-toughness cement-based composite and preparation method thereof
CN109133796A
Lightweight high-strength concrete and preparation method thereof
CN112521095A
Sprayable PVA-ECC high-ductility cement-based composite material and preparation method thereof
CN112745085A
Lightweight high-ductility cement-based composite material capable of being used for 3D printing and preparation method thereof
CN112876165A
Multi-scale-reinforced lightweight high-ductility cement-based composite material and preparation method thereof
CN114057456A
Cited By
Super-early-strength and high-toughness sprayed concrete and preparation method thereof
CN121929968A
An ultra-early-strength, high-toughness shotcrete and a preparation method thereof
CN121929968B
